Current State and Forecasting of the Development of Bank Crediting in Kazakhstan - Kalkabayeva, Gauhar; Kurmanalina, Anar; Gusmanova, Zhanar (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The article analyzes the state of bank lending in Kazakhstan in comparison with other countries as a developed economy, as well as with the emerging market.The modern tendencies of development of bank crediting of economy are considered. The necessity of activization of credit activity of Kazakhstan banks with the purpose of ensuring stable economic growth is substantiated. The reasons for the low interest of banks in lending to enterprises in the real sector of the economy are disclosed. The factors influencing the volumes of bank lending in the Republic of Kazakhstan are revealed, their significance is estimated using correlation-regression analysis.